Democracy Development in Tunisia During President of Kais Saied - Mohamad Fuat Najib; Subaidi Subaidi (Universitas of Muhammadiyah Makassar, 2023)
After general election, fair and competitive elections in 2019 with the election of Kais Saied as president, Tunisia's democracy has been a success. However, political turmoil arose after President Saied's political actions by issuing emergency decrees; dissolving parliament, removing the prime minister and controlling executive institutions were considered to hinder democratic development in Tunisia. This research looks at the elements of democratization development using Robert Dahl's theory of democracy on the one hand and on the other hand will look at President Saied's autocratic actions using Levitsky and Ziblatt's theory of otritarianism. The method used in this research is a microscopic research method, which looks at parts of President Saied's political actions in the democratization process in Tunisia. The results of this study indicate that the democratization process in Tunisia is considered to have been successful as seen from the implementation of elections, public participation and freedom of the press. However, the development of democracy has stagnated due to actions that occurred after President Saied issued decrees such as rejection of the democratic system, control of the media and repressive actions showing the decline of democratic values in Tunisia towards authoritarianism. This shows the decline of democratization principles in Tunisia after the achievements obtained after the Arab Spring.